Social Engagement After Nursing Home Admission: Racial and Ethnic Disparities and Risk Factors. (November 2017) - Bliss, Donna; Harms, Susan; Eberly, Lynn E.; Savik, Kay; Gurvich, Olga; Mueller, Christine; Wyman, Jean F.; Virnig, Beth
Older adults admitted to nursing homes (NHs) are at risk for low social engagement, which has associations with medical, psychological, and social well-being. Minorities may be at a disadvantage for social engagement because of their racial or ethnic group identity. This study assessed whether there were racial/ethnic disparities in social engagement among older adults ( N = 15, 927) at 1 year after their NH admission using multi-level predictors. No racial or ethnic-based disparities in social engagement were found; hence, an analysis of risk factors at NH admission that predicted low social engagement at 1 year for all residents was conducted. Significant risk factors for low social engagement were low social engagement at admission, deficits in activities in daily living and cognition, problems with vision and communication, and residing in an NH in an urban community. Results highlight the importance of initiating interventions to increase social engagement at the time of NH admission.